Analgesia and Sedation Requirements in Mechanically Ventilated Trauma Patients With Acute, Preinjury Use of Cocaine and/or Amphetamines. (March 2017) - Kram, Bridgette; Kram, Shawn J.; Sharpe, Michelle L.; James, Michael L.; Kuchibhatla, Maragatha; Shapiro, Mark L.
Abstract : BACKGROUND: The purpose of this study was to determine whether mechanically ventilated trauma patients with a positive urine drug screen (UDS) for cocaine and/or amphetamines have different opioid analgesic and sedative requirements compared with similar patients with a negative drug screen for these stimulants. METHODS: This retrospective, single-center cohort study at a tertiary care, academic medical and level 1 trauma center in the United States included patients ≥16 years of age who were admitted to an adult intensive care unit with a diagnosis of trauma between 2009 and 2013 with a UDS documented within 24 hours of admission, and were mechanically ventilated for >24 hours. The primary end point was the daily dose of opioid received during mechanical ventilation, expressed as morphine equivalents, for patients presenting with a positive UDS for cocaine and/or amphetamines compared with patients with a negative UDS for these stimulants. Secondary end points included the daily benzodiazepine dose and median infusion rates of propofol and dexmedetomidine received during mechanical ventilation, duration of mechanical ventilation, intensive care unit and hospital length of stay, and in-hospital mortality. Analgesic and sedative goals were similar for the duration of the study period, and both intermittent and continuous infusions of opioids and sedatives were administered to achieve these targets, although a standardized approach was not used. A multivariate logistic regression analysis and a propensity-adjusted model evaluated patient characteristics predictive of a higher median opioid requirement. RESULTS: A total of 150 patients were included in the final analysis. In a univariate analysis, opioid and sedative requirements were similar for patients presenting with a positive UDS for cocaine and/or amphetamines compared with patients with a negative UDS for these stimulants. In the multivariate regression analysis, increasing age and Abbreviated Injury Scale (head and neck) were associated with decreased daily opioid requirements (odds ratio [OR], .95, 95% confidence interval [CI], .93–.97 and OR, .71, 95% CI, .65–.77, respectively), whereas preinjury stimulant use was not predictive of opioid requirements (OR, .88, 95% CI, .40–1.90). In a propensity score–adjusted model, preinjury stimulant use was similarly not predictive of opioid requirements during mechanical ventilation (OR, .97, 95% CI, .44–2.11). CONCLUSIONS: For trauma patients presenting with acute, preinjury use of cocaine and/or amphetamines, analgesic and sedative requirements are variables and may not be greater than those patients presenting with a stimulant-negative UDS to achieve desirable pain control and depth of sedation, although this observation should be interpreted cautiously in light of the wide CI observed in the propensity score–adjusted model. Although unexpected, these findings indicate that empirically increasing analgesic and sedative doses based on positive UDS results for these stimulants may not be necessary. Abstract : Supplemental Digital Content is available in the text.